Governance Mechanisms, Sustainability Reporting, and Investor Confidence: The Mediating Role of Information Risk - Andi Aris Mattunruang; Rahmawati Rahmawati; Inayah Abdillah Rabbani; Nurul Afiqah Annas (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study examines the role of corporate governance mechanisms in reducing information risk and enhancing investor confidence through sustainability reporting. The topic is important as increasing ESG disclosure requirements and market expectations have intensified the need for transparent and credible corporate reporting to mitigate information asymmetry in emerging markets. Design/methodology/approach – Research employs a quantitative approach using panel data from 35 firms listed in the Indeks SRI-KEHATI over the period 2018–2024, resulting in 245 observations. Panel data regression is used to analyze the effect of governance mechanisms on information risk, while Structural Equation Modeling (SEM-PLS) is applied to examine direct and mediating relationships among variables. Finding/Results – The results indicate that governance mechanisms significantly reduce information risk, particularly through independent commissioners, board size, and institutional ownership. Furthermore, information risk plays a significant mediating role in strengthening investor confidence, as lower information asymmetry leads to higher market trust. Originality/Value – This study provides empirical evidence on the mediating role of information risk in the relationship between governance mechanisms and investor confidence within the context of sustainability reporting. The findings highlight that effective governance and transparent ESG disclosure are not only regulatory requirements but also strategic tools to enhance market credibility and investor trust in emerging markets.